Ethics of fetal tissue transplantation. - Sanders, L M (1993)
Now that the Clinton Administration has overturned the ban on federal funding for fetal tissue transplantation, old ethical issues renew their relevance and new ethical issues arise. Is fetal tissue transplantation necessary and beneficial? Are fetal rights violated by the use of fetal tissue in research? Is there a moral danger that the potential of fetal tissue donation will encourage elective abortions? Should pregnant women be allowed to designate specific fetal transplant recipients? What criteria should be used to select fetal tissue transplants? Whose consent should be required for the use of fetal tissue for transplantation? We review the current state of clinical research with fetal tissue transplantation, the legal history of fetal tissue research, the major arguments against the use of fetal tissue for transplantation, and the new postmoratorium ethical dilemmas. We include recommendations for guidelines to govern the medical treatment of fetal tissue in transplantation.